Genitourinary Cancers: Molecular Determinants for Personalized Therapies. Issue 3 (July 2016) - Mazzucchelli, Roberta; Gasparrini, Silvia; Galosi, Andrea B.; Massari, Francesco; Raspollini, Maria Rosaria; Scarpelli, Marina; Lopez-Beltran, Antonio; Cheng, Liang; Montironi, Rodolfo
Recent insights and emerging strategies for individualized therapeutic approaches in patients with genitourinary (GU) cancers are based on patient's genomic and cancer's molecular profiles. This depends on the significant advances made in molecular biology technologies, such as next-generation sequencing and whole-exome sequencing. The rise of such novel techniques has grayly increased our knowledge on cancer cell biology and development, thus allowing to identify complex abnormalities at the genomic level. These findings have paved the way toward what is called precision medicine, thus providing healthcare from an individual perspective in patients with GU tumors.